Molecular mechanism underlying cardioprotective effect of dehydroepiandrosterone on endoplasmic reticulum stress induced apoptosis in human vascular smooth muscle cells and human umbilical vein endothelial cells - Zhu, Ye; Wei, Junxiu; Yang, Xin; Zhu, Wei (Frontiers in Pharmacology, 2025)
IntroductionThis study aimed to investigate the underlying mechanisms involved in the cardioprotective effects of dehydroepiandrosterone (DHEA) on endoplasmic reticulum stress (ERS) -mediated apoptosis in human vascular smooth muscle cells (HVSMCs) and human umbilical vein endothelial cells (HUVECs).Material and methodsVarious concentrations of Dithiothreitol (DTT) were used to induce ERS-mediated apoptosis. DHEA was utilized to inhibit the apoptotic effects of DTT, while estrogen receptor (ER) antagonists ICI 182,780 and G15, the androgen receptor (AR) antagonist flutamide and the aromatase inhibitor letrozole were used to identify the receptors activated during DHEA treatment in HVSMCs and HUVECs. Flow cytometry assessed the apoptotic rate, and Western blotting analysis evaluated the expression levels of ERS-related proteins GRP78 and PERK, and the apoptotic protein marker CHOP. Furthermore, the primary receptor signaling pathways were identified using signaling pathway blockers: LY294002 (PI3K blocker), SP600125 (JNK blocker), and U0126 (ERK1/2 blocker).ResultsIn the DTT pretreatment group (0.8 mmol/L, for 8 h), the expressions of GRP78 and CHOP were significantly up regulated, indicating that an optimal ERS model was successfully established. Additionally, 10-4 mmol/L DHEA significantly inhibited the DTT-induced upregulation of GRP78 and CHOP. The results also demonstrated that the apoptotic rate in the DTT group was increased, while DHEA significantly reduced this rate. The addition of ER antagonists ICI 182,780 and G15 to HVSMCs reversed the effects of DHEA; however, the aromatase inhibitor letrozole and the AR antagonist flutamide did not reverse this effect. Notably, the use of the JNK inhibitor SP600125, the PI3K inhibitor LY294002, and the ERK1/2 inhibitor U0126 antagonized the protective effects of DHEA, with SP600125 showing the most significant impact on both HVSMCs and HUVECs.ConclusionOur study has identified a novel mechanism underlying the cardioprotective effects of DHEA. Specifically, DHEA may mitigate ERS-induced cell apoptosis by activating estrogen receptors ERα, ERβ, and GPER via the activated JNK pathway.